Building confidence in the metaverse: Implementation and evaluation of a multi-user virtual reality application for overcoming fear of public speaking - Laine, Teemu H.; Lee, Woohyun; Moon, Jiyoung; Kim, Eunha (International Journal of Human Computer Studies, 2025)
Fear of public speaking is a social anxiety disorder that causes individuals to fear speaking in front of crowds, significantly impacting their education, work, and psychological wellbeing. Immersive virtual reality (VR) has emerged as a potential tool for addressing this fear by simulating public-speaking scenarios in a controlled environment. However, previous VR solutions for public-speaking anxiety have been single-user and lacked multimodal data collection. This study proposed Ready Player Speak, a novel multi-user VR exposure therapy application designed for people who experience fear of public speaking, incorporating data collection through questionnaires and sensors. We evaluated Ready Player Speak in a mixed-method user study with 32 young adult participants who delivered interactive speeches in front of an audience comprising human- and computer-controlled avatars. Participants completed pre- and post-test questionnaires and were interviewed at the end. The user study results indicated that Ready Player Speak felt realistic, and most participants experienced a sense of spatial presence. However, the realism of the avatars and their appropriateness were criticized. Nevertheless, Ready Player Speak had a statistically significant lowering effect on the fear of public speaking experienced by the participants, indicating its potential as a tool for addressing this fear. Based on the evaluation results and our experiences with the development of Ready Player Speak, we presented 12 lessons learned. This study's findings can inform researchers and developers seeking to harness multi-user VR exposure therapy for fear of public speaking and other psychology interventions.
Keywords: Data collection; Fear of public speaking; Metaverses; Multiusers; Presence; Public speaking; Social anxieties; User study; Users' experiences; Virtual reality exposure therapies; Fear of public speaking; Metaverse; Multi-user; Presence; User experience; Virtual reality